Ultrasound assessment of normal splenic length and spleen to left kidney ratio in sample of Iraqi population - Al-timimy, Qays A.; Al-Naddawi, Mahjoob N.; Joori, Salam M. (AL-Kindy College Medical Journal, 2014)
Background: Spleen is a hemopoietic organ which is capable of supporting elements of different systems. It is affected by several groups of diseases; inflammatory, hematopoietic, reticuloendothelial proliferation, portal hypertension and storage diseases. Ultrasound (US) may detect mild splenomegaly before it is clinically palpable. Knowledge of the normal range of spleen size in the population being examined is a prerequisite. Racial differences in splenic length could result in incorrect interpretation of splenic measurements and such differences would make it difficult to standardize expected splenic length and to determine non- palpable splenic enlargement.Objectives: To measure the normal values of splenic lengthin Iraqi subjects and compare the results with western,Chinese and Jordanian data; to determine whether there is aconstant ratio of the length of the spleen to the left kidney,which could be used to diagnose splenomegaly withoutreference to a nomogram.Methods: This is a cross-sectional study conducted among a total of 280 subjects ranging in age from birth to 20 years (159 males and 121 females). US was used to measure maximum splenic and left kidney lengths to obtain normal values for splenic length and to determine spleen to left kidney ratio. The subjects were divided into the same age groups as those used by other similar international studies in order that comparisons with their results could be made.Results: Splenic lengths in Iraqi subjects are similar to those in American, Chinese and Jordanian subjects up to the age of 15 years. The spleen to left kidney ratio is strikingly constant with a mean value of 1. Using 2 SD above the mean as a guide, the upper limit of normal for spleen to left kidney ratio is 1.25.Conclusion: Splenomegaly should be suspected in children if the spleen is more than 1.25 times longer than the adjacent kidney.Key words: Spleen, subjects, ultrasound